Trade Liberalization and Poverty: A Macro-Micro Analysis in Ethiopia - Sindu Kebede; Belay Fekadu; Dejene Aredo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Using a CGE model, this study analyses the impact of trade liberalization on poverty at the household level taking Ethiopia as a case. Two scenarios (complete tariff cut and uniform tariff scheme) suggest that further liberalization of trade has little short-run effect on the overall economy. However, the agriculture-based manufacturing sector (in particular, textile and leather) is likely to be strongly affected by further tariff reduction. Reductions in import prices of textiles and leather products increase imports of these goods implying that trade liberalization is likely to dampen domestic production of textile and leather products. Poverty shows a slight increase in both scenarios. At the national level, a complete tariff cut results in an increase in poverty by 2.8 percent, while a uniform tariff scheme raises poverty by 2.3 percent. Similarly, it is found that poverty gap and poverty severity indices show a slight increase. Comparing the effect of trade reform on different household groups, i.e. farm households, wage earner households and entrepreneur households, poverty in entrepreneur households increases by a higher percentage change (3.2 percent) in the complete tariff cut scenario. Poverty incidence increases by 1.7 and 1.5 percent for farm households and wage earners, respectively, under the complete tariff cut scenario. This comparison holds consistently when looking at the more realistic uniform tariff scheme. Entrepreneur households are at a disadvantage due to trade liberalization shown in the poverty gap and poverty severity indices. This is consistent with the theoretical argument that previously protected infant industries are highly affected by trade liberalization.
Keywords: 330; trade liberalization; poverty; CGE; import duties; macro-micro simulation